Service conversation: advisory, relational and transformative approaches. Issue 8 (27th January 2021) - Gopaldas, Ahir; Carnevale, Marina; Kedzior, Richard; Siebert, Anton
Abstract : Purpose: The marketing literature on service conversation in dyadic services has elaborated two approaches. An advisory approach involves providers giving customers expert advice on how to advance difficult projects. By contrast, a relational approach involves providers exchanging social support with customers to develop commercial friendships. Inspired by the transformative turn in service research, this study aims to develop a third approach, one that helps customers to cultivate their own agency, potential and well-being. Design/methodology/approach: The emergent model of service conversation is based on in-depth interviews with providers and clients of mental health services, including psychological counseling, psychotherapy and personal coaching. Findings: A transformative approach to service conversation involves the iterative application of a complementary pair of conversational practices: seeding microtransformations by asking questions to inspire new ways of thinking, feeling and acting; and nurturing microtransformations via non-evaluative listening to affirm customers' explorations of new possibilities. This pair of practices immediately elevates customers' sense of psychological freedom, which, in turn, enables their process of self-transformation, one microtransformation at a time. Practical implications: This study offers dyadic service providers a conceptual framework of advisory, relational and transformative approaches to service conversation for instrumental, communal and developmental service encounters, respectively. This framework can help dyadic service providers to conduct more collaborative, flexible and productive conversations with their customers. Originality/value: Three approaches to service conversation – advisory, relational and transformative – are conceptually distinguished in terms of their overall aims, provider practices, customer experiences, customer outcomes, allocations of airtime, designations of expertise, application contexts, prototypical examples and blind spots.